Metallic Conductive Nanowires Elaborated by PVD Metal Deposition on Suspended DNA Bundles. Issue 33 (5th July 2017) - Brun, Christophe; Elchinger, Pierre‐Henri; Nonglaton, Guillaume; Tidiane‐Diagne, Cheikh; Tiron, Raluca; Thuaire, Aurélie; Gasparutto, Didier; Baillin, Xavier
Abstract : Metallic conductive nanowires (NWs) with DNA bundle core are achieved, thanks to an original process relying on double‐stranded DNA alignment and physical vapor deposition (PVD) metallization steps involving a silicon substrate. First, bundles of DNA are suspended with a repeatable process between 2 µm high parallel electrodes with separating gaps ranging from 800 nm to 2 µm. The process consists in the drop deposition of a DNA lambda‐phage solution on the electrodes followed by a naturally evaporation step. The deposition process is controlled by the DNA concentration within the buffer solution, the drop volume, and the electrode hydrophobicity. The suspended bundles are finally metallized with various thicknesses of titanium and gold by a PVD e‐beam evaporation process. The achieved NWs have a width ranging from a few nanometers up to 100 nm. The electrical behavior of the achieved 60 and 80 nm width metallic NWs is shown to be Ohmic and their intrinsic resistance is estimated according to different geometrical models of the NW section area. For the 80 nm width NWs, a resistance of about few ohms is established, opening exploration fields for applications in microelectronics. Abstract : Suspended metallic and conductive nanowires composed of a DNA bundle core are achieved, thanks to an original process relying on double‐stranded DNA alignment and PVD metallization steps. Various thicknesses from a few to hundreds of nanometers of titanium and gold layers covering the suspended DNA‐based nanowires are fabricated in a repeatable process. Electrical measurements prove the ohmic behavior of such nanowires.